Teaching Our Youngest A Guide for Preschool Teachers, Child Care & Family Providers / Bonnie Armbruster, Fran Lehr and Jean Osborn. - Armbruster, Bonnie (Distributed by ERIC Clearinghouse, 2002)
Noting that everyone who interacts with a young child is a teacher, this booklet for preschool teachers and child care providers draws from scientifically based research about what they can do to help children develop their language abilities, increase their knowledge, become familiar with books and other printed materials, learn letters and sounds, recognize numbers, and learn to count. The booklet provides examples of ways to create an environment in the preschool classroom that will nurture children's natural curiosity and their zest for learning. Following an introduction, the booklet's sections cover: (1) Creating the Learning Environment for Young Children; (2) Reading Aloud to Children; (3) Developing Listening and Speaking Skills; (4) Teaching about the Sounds of Spoken Language; (5) Teaching about Print; (6) Teaching about Books; (7) Teaching about Letters; (8) Building Children's Background Knowledge and Thinking Skills; (9) Teaching about Numbers and Counting; (10) Checking Children's Progress; (11) Communicating with Parents and Caregivers; and (12) Some Helpful Terms To Know. The booklet concludes with a list of suggested readings on early childhood education. (HTH)